PENERAPAN SANKSI HUKUM ADAT CAPA MOLOT TERHADAP PELANGGAR BALALA DI DESA KAYU ARA KECAMATAN MANDOR - NIM. A1012181172, RIEZKY DWI CAHYO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Violation of the Balala' traditional ritual is considered an act that can disrupt the balance and harmony of the community, as well as their relationship with the ancestral spirits of the Dayak Kanayatn tribe. One of the customary problems that has occurred in Kayu Ara village during the implementation of balala is capa molot or the spread of false news. This study uses an empirical legal approach with a descriptive-qualitative approach through interviews with traditional leaders, analysis of customary law documents, and direct observation of the practice of implementing sanctions. Based on the research that the researcher found, the Dayak Kanayatn community in Kayu Ara village still carries out the balala' traditional ritual every year. Several violations were found related to this activity, this violation is called capa molot, or an insult to the balala' traditional ritual. The imposition of sanctions is determined by the traditional elders/Timanggunk. The resolution of this conflict is by paying a customary fine of 1 tangah which is equivalent to Rp. 800,000.00. This study confirms that the customary law of Dayak Kanayatn is still maintained in the life of the community, especially in resolving conflicts with a restorative approach that focuses more on restoring social relations. Therefore, a more inclusive policy is needed to accommodate customary law in the national legal system so that the sustainability of customary law traditions can be maintained without conflicting with the principles of the rule of law. Keywords: Capa Molot, Dayak Kanayatn, Law Abstrak Pelanggaran terhadap ritual adat Balala